TGF-β Signaling Interferes With the Drosophila Innate Immune and Metabolic Response to Parasitic Nematode Infection - Ozakman, Yaprak; Eleftherianos, Ioannis (Frontiers in Physiology, 2019)
The common fruit fly, Drosophila melanogaster, is an outstanding model to study the molecular basis of anti-pathogen immunity. The parasitic nematode Heterorhabditis gerrardi, together with its mutualistic bacteria Photorhabdus asymbiotica, infects a wide range of insects, including D. melanogaster. Recently we have shown that Transforming Growth Factor-β (TGF-ß) signaling in D. melanogaster is regulated in response to parasitic nematode infection. In the current study, we investigated the contribution of two TGF-ß signaling branches, the activin and the Bone Morphogenic Protein (BMP), to D. melanogaster immune function against H. gerrardi. We used D. melanogaster larvae carrying mutations in the genes coding for the TGF-ß extracellular ligands daw and dpp. We have demonstrated that the number of circulating hemocytes in uninfected daw and dpp mutants decreases 2-fold compared to background controls, yet no significant changes in hemocyte numbers and survival of the TGF-ß mutants are observed upon nematode infection. However, we have shown that nematode-infected daw mutants express Dual oxidase at higher levels and phenoloxidase activity at lower levels compared to their background controls. To elucidate the contribution of TGF-ß signaling in the metabolic response of D. melanogaster to parasitic nematodes, we estimated lipid and carbohydrate levels in daw and dpp mutant larvae infected with H. gerrardi. We have found that both nematode-infected mutants contain lipid droplets of larger size, with daw mutant larvae also containing elevated glycogen levels. Overall, our findings indicate that the regulation of activin and BMP branches of TGF-ß signaling can alter the immune and metabolic processes in D. melanogaster during response to parasitic nematode infection. Results from this study shed light on the molecular signaling pathways insects activate to regulate mechanisms for fighting potent nematode parasites, which could lead to the identification of novel management strategies for the control of damaging pests.